First Impressions Matter: How Initial Worries Influence Adherence to the Dapivirine Vaginal Ring. (1st July 2019) - van der Straten, Ariane; Browne, Erica N.; Shapley-Quinn, Mary Kate; Brown, Elizabeth R.; Reddy, Krishnaveni; Scheckter, Rachel; Soto-Torres, Lydia; Palanee-Phillips, Thesla; Baeten, Jared M.; Mensch, Barbara
Abstract : Background: In MTN-020/ASPIRE, a dapivirine vaginal ring effectiveness trial in sub-Saharan Africa, we assessed whether worries about ring use changed over time and were associated with adherence. Methods: Participants (N = 2585) were surveyed at baseline and follow-up about worries regarding daily ring use. First, they answered a question about general worries and then responded to 15 items covering specific worries. From a nested qualitative component (N = 214), we extracted themes related to ring worries and adherence. Seven months into the trial, aggregate adherence data were shared with study sites as part of an intervention that included counseling and social support. Nonadherence was defined as dapivirine plasma levels of ⩽95 pg/mL. Mixed-effect logistic regression models were used to assess changes in ring worries and nonadherence from baseline to month 3 and later. Results: Worry about wearing the ring decreased from 29% at baseline to 4% at month 3 ( P < 0.001), while having a specific worry decreased from 47% to 16% ( P < 0.001). Among those enrolled before intervention, 29% with baseline worries were nonadherent at month 3 (95% confidence interval: 19% to 39%) compared to 14% without worries (95% confidence interval: 9% to 19%; P = 0.005); the difference persisted through month 6. There was no difference in nonadherence by baseline worry for those enrolled after intervention ( P = 0.40). In the qualitative subset, initial ring anxieties reportedly subsided with self-experimentation and practice and the beneficial influence of the intervention. Conclusions: Although worries may be an initial deterrent to correct ring use, intervening early by leveraging social influences from peers and clinicians should facilitate successful adoption and correct ring use.